Prevalence and Risk Factors of Suicidal Ideation among Patients with Head and Neck Cancer: Longitudinal Study. (5th June 2018) - Henry, Melissa; Rosberger, Zeev; Bertrand, Lia; Klassen, Christina; Hier, Michael; Zeitouni, Anthony; Kost, Karen; Mlynarek, Alex; Richardson, Keith; Black, Martin; MacDonald, Christina; Zhang, Xun; et al.
Abstract : Objectives: (1) Determine 1‐year period prevalence of suicidal ideation, suicide attempt, and completed suicide among patients newly diagnosed with a first occurrence of head and neck cancer (HNC). (2) Characterize stability and trajectory of suicidal ideation over the year following cancer diagnosis. (3) Identify patients at risk of suicidal ideation. Study Design: Prospective longitudinal study with 1‐year follow‐up. Setting: Three university‐affiliated outpatient departments of otolaryngology–head and neck surgery. Subjects and Methods: The study comprised a representative sample of 223 consecutive patients who were newly diagnosed (<2 weeks) with a first occurrence of primary HNC, were ≥18 years old and able to consent, and had a Karnofsky Performance Scale score ≥60. Patients completed the Beck Scale for Suicidal Ideation and Structured Clinical Interview for DSM‐IV‐TR Axis I Disorders. Results: Sixteen percent (15.7%) of patients with HNC were suicidal <1 year from diagnosis, with point prevalences of 8.1% <2 weeks, 14.8% at 3 months, 9.4% at 6 months, and 10.4% at 12 months; 0.4% committed suicide within 3 months, and 0.9% attempted suicide. An a priori comprehensive conceptual model revealed 2 predictors of 1‐year period prevalence of suicidal ideation in HNC: psychiatric history ( P =. 017, β = 2.1, 95% CI = 0.4‐3.8) and coping with the diagnosis by using substances (alcohol/drugs; P =. 008, β = 0.61, 95% CI = 0.16‐1.06). All other predictors, including medical predictors, were nonsignificant. A clinical suicide risk assessment revealed low risk among 71.4% and medium to high risk among 28.6%. Conclusion: Suicide prevention strategies are clearly needed as part of routine clinical care in head and neck oncology, as well as their integration into clinical practice guidelines for HNC.